Redox-responsive microbeads containing thiolated pectin-doxorubicin conjugate inhibit tumor growth and metastasis: An in vitro and in vivo study - Cheewatanakornkool, K.; Niratisai, S.; Dass, Crispin; Sriamornsak, P. (Elsevier BV, 2018)
© 2018 The objective of this study was to investigate the in vitro cytotoxicity and in vivo anticancer efficacy of redox-responsive microbeads containing thiolated pectin–doxorubicin (DOX) conjugate. Oral microbeads were coated with an enteric polymer to protect the drug from release in the upper gastrointestinal (GI) tract and allow redox-triggered drug release in the colon. Morphology, particle size, drug content, and in vitro drug release behavior of the microbeads were characterized; in vitro cytotoxicity was tested on mouse colon carcinoma, human colorectal adenocarcinoma, and human bone osteosarcoma cell lines. In vivo anticancer efficacy of coated microbeads was examined in BALB/c mice with murine colon carcinoma. These coated microbeads significantly inhibited the growth of all cell lines. The in vivo study confirmed delivery of DOX to the colorectal tumor site, redox-responsiveness, and anticancer efficacy of coated microbeads. Coated microbeads also effectively inhibited primary tumor growth and suppressed tumor metastases without gross toxicity to the non-target tissue. No noticeable damage was found in mouse GI tissues, indicating lack of DOX toxicity. These novel coated microbeads containing thiolated pectin–DOX conjugate may be a promising vehicle for targeted clinical delivery of DOX to the colorectal cancer site by oral administration.